1981
DOI: 10.1902/jop.1981.52.4.187
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gingival Tissue Temperatures and Various Indicators of Gingival Inflammation

Abstract: IN PERIODONTICS there is a need for objective measurements in monitoring disease processes and in assessing the effectiveness of treatment. The purpose of this study was to compare gingival temperatures with indicators of gingival inflammation in order to examine the application of temperature as a diagnostic aid. In six patients the temperature of interproximal sulcular tissue was measured and compared with bleeding upon probing, crevicular fluid flow, pocket depth, plaque accumulation and calculus formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 4 publications
4
11
0
Order By: Relevance
“…In full mouth assessments, 86% of diseased subjects (sensitivity) and 91% of healthy subjects (specificity) were recognized correctly by the temperature technique. These results are consistent with reported higher temperatures in inter- proximal sulcular tissue With the presence of dental plaque and bleeding on probing (Holthius et al 1981). Sensitivity and specificity levels are clearly a function of the classification of the diseased state based on BOP, suppuration, and attachment level.…”
Section: Discussion and Summarysupporting
confidence: 90%
“…In full mouth assessments, 86% of diseased subjects (sensitivity) and 91% of healthy subjects (specificity) were recognized correctly by the temperature technique. These results are consistent with reported higher temperatures in inter- proximal sulcular tissue With the presence of dental plaque and bleeding on probing (Holthius et al 1981). Sensitivity and specificity levels are clearly a function of the classification of the diseased state based on BOP, suppuration, and attachment level.…”
Section: Discussion and Summarysupporting
confidence: 90%
“…We found that T. denticola cells swim considerably faster and grow better at 35³C than at 25³C. Because the prevailing temperature of the gingival sulcus is approximately 35³C [16], our results are consistent with this oral pocket serving as the ecological niche for these spirochetes [2]. The speed of intestinal spirochetes has also been shown to be markedly in£uenced by temperature [17,18].…”
Section: Resultssupporting
confidence: 81%
“…5-7). (Mukherjee 1978, Ng et al 1978, Holthuis et al 1981, Volchansky et al 1985, Volchansky & Cleaton-Jones 1987, Kung et al 1990) that the average subgingival temperature was almost 2°C lower than the sublingual temperature. In addition, there was a great deal of variation of temperatures between teeth as pointed out previously.…”
Section: Relationship Of Mean Subgingivai Temperatures To Ciinicai Pamentioning
confidence: 96%
“…Temperature is one of the more attractive methods of evaluating this response, since it lends itself to direct physical measurement. A number of devices have been developed to measure subgingival temperature (Mukherjee 1978, Ng et al 1978, Holthuis et al 1981, Volchansky et al 1985, Volchansky & Cleaton-Jones 1987, Kung et al 1990. These studies described a number of interesting features of subgingival temperature measurements.…”
mentioning
confidence: 99%